Rapid Screening of 60 Types of Natural Toxins in Whole Blood by UPLC-Q/Orbitrap HRMS - GUO Zhu-tao; DENG Qian-ya; HE Si-yang; ZHENG Shui-qing; WANG Rong; SUN Wen-juan; LIANG Chen; NI Chun-fang (Fayixue Zazhi)
ObjectiveTo establish a rapid screening method for 60 types of natural toxins in whole blood by ultra-high performance liquid chromatography-quadrupole/electrostatic field orbitrap high resolution mass spectrometry （UPLC-Q/Orbitrap HRMS).MethodsThe chromatographic and mass spectrometric information of 60 standard samples of natural toxins were analyzed and recorded, and a screening database was built. Whole blood was pretreated by protein precipitation method combined with ultrasonic-assisted dispersion, and then a Hypersil GOLDTM C18 column was used with 5 mmol/L ammonium formate aqueous solution （containing 0.1% formic acid） and acetonitrile as mobile phase for gradient elution. In the positive ion mode, the data were collected in full scan/data-dependent secondary scan （Full MS/dd-MS2） mode. Based on the established screening library, the rapid screening of 60 types of natural toxins in whole blood was realized by TraceFinder software.ResultsA UPLC-Q/Orbitrap HRMS method was developed for the screening of 60 types of natural toxins in whole blood. Except for the limit of detection （LOD） of oxymatrine （20 ng/mL） and strophanthidin （40 ng/mL）, the LOD for the other 58 natural toxins was in the range of 0.05-5 ng/mL.ConclusionThis method has a simple and efficient pretreatment process and can achieve rapid screening of 60 types of natural toxins in whole blood.